THEMATIC-CONTENT TYPES OF SYNTACTIC CONSTRUCTIONS WITH ALIEN SPEECH IN THE EPIC “MANAS” (BASED ON S. OROZBAKOV’S VERSION) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The subject of this scientific article is the language of the epic “Manas”, and its main object is thematic-content types of syntactic constructions with someone else’s speech in the epic. The purpose of this work is to study the thematic and content types of constructions with alien speech used in the epic “Manas” in the version of the great storyteller S. Orozbakov. Based on the methods of analysis and synthesis, comparison, narration, the alien speech used in the epic is divided into 8 thematic and content types. This is: a conversation between two or three people, a dialogue-narration; inner thought, monologue; blessing; winged words, proverb; gossip, legend; slogan, challenge; letter.
Keywords: epos, “Manas”, alian speech, construction with alian speech, thematic and content types, analysis, dialogue-narration, monologue, blessing, catchphrase, proverb, gossip, gossip, slogan, letter